The Effects of Collecting Income Taxes on Social Security Benefits - John Bailey Jones; Yue Li (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2017)
Since 1983, Social Security benefits have been subject to income taxation, a provision that can significantly increase the marginal income tax rate for older individuals. To assess the impact of this tax, we construct and calibrate a detailed life-cycle model of labor supply, saving, and Social Security claiming. We find that in a long-run stationary environment, replacing the taxation of Social Security benefits with a revenue-equivalent change in the payroll tax would increase labor supply, consumption, and welfare. From an ex-ante perspective an equally desirable reform would be to make the portion of benefits subject to income taxes completely independent of other income.
Keywords: E21; H24; H55; I38; 330; Social Security; Labor Supply; Taxation